Pemanfaatan Limbah Ikan Sebagai Pupuk Organik Cair (POC) Dengan Penambahan Kulit Buah Nanas Dan Air Cucian Beras - Rafidah rafidah; Ayu Apriliyanti; Hidayat; Zaenab (Sulolipu: Media Komunikasi Sivitas Akademika dan Masyarakat, 2023)
The amount of fish waste in the form of fish washing water used by the community resulted in the disposal of more fish waste per day the more increased. Disposal of fish waste to the environment in a manner direct without existing processing no only will raise the smell of very rotten sting but also can bother the environment. Study this aims to know the utilization of fish waste into POC with the addition of skin pineapple and washing water rice. Type research used in the study this is experiment pseudo (Quasi-Experimental) with conducted trials on fish waste with the addition of skin pineapple and washing water rice. The results of research on the manufacture of fish waste POC, fish waste POC with the addition of skin pineapple and washing water rice for 21 days is in quality physique smell fishy (no fulfill terms) and color yellow brownish (fill condition) whereas quality chemistry on POC fish waste with addition skin pineapple fruit yield NPK value (N+P2O5 +K2O) = 0.35%, in POC fish waste with adding washing water rice results NPK value (N+P2O5 +K2O) = 0.28%, and POC fish waste NPK value (N+P2O5 +K2O) = 0.55% stated low or No fulfill standards and pH complied standard. Deep conclusion study this is fish waste with the addition of skin pineapple and washing water rice can be used as POC. It is hoped that researchers furthermore vary time decomposition to become material measuring in the process of becoming POC and selecting material organic containing a high NPK value